Investigation of Rutting Resistance of Asphalt Mixture Containing Crumb Rubber - RASIDIN, NUR NAJWA; BUHARI, ROSNAWATI (Recent Trends in Civil Engineering and Built Environment, 2022)
There are two techniques have been used to add crumb rubber to bituminous mixes. That are wet process and dry process. Dry process was conducted by adding the crumb rubber directly to the aggregate as another ingredient in the mix. Dry process is conducted by Superpave mix design. It has potential to consume larger quantities of recycled crumb rubber compared to the wet process resulting in greater environmental benefits. Although, rutting was frequently reported while applying rubberised mixture for pavement and has become one of the major distress forms with the increase in traffic volume, tire pressure and axial load. Therefore, the objective of this study is to investigate the performance of tyre rubber in asphalt mixture for rutting resistance based on laboratory test results from previous study. In accordance, the result show that the mixes with the lowest mean final deformation values were those with the largest percentages of crumb rubber and the use of crumb rubber in bituminous mixes is effective and significantly improves mix response to plastic deformation. The addition of crumb rubber in the aggregate asphalt mixture and has achieved better-modified asphalt mixture performance and higher rutting resistance than asphalt mixture without crumb rubber.